Burn Injuries in Hospitalized Australian Children - An Epidemiological Profile - Ryder, C; Mackean, T; Hunter, K; Rogers, K; Holland, AJA; Ivers, R (Journal of Burn Care & Research, 2021)
Globally, First Nations children sustain burns at a higher rate than other children. Little is understood about how health inequities contribute, especially from an Indigenous viewpoint. We analyzed data from the Burns Registry of Australian and New Zealand (BRANZ) for acute burns in children (<16 years) admitted to hospital between October 2009 and July 2018. Descriptive statistics examined equity variables in patient and injury characteristics. Poisson regression was used to describe factors associated with bacterial infection. Indigenous research methods were used throughout. Aboriginal and Torres Strait Islander children represented 10.4% of the study population. Health inequities were present for Aboriginal and Torres Strait Islander children with longer hospital length of stay (9.5 vs 4.6 days), rural residency (61.3% vs 13.9%), lower socioeconomic status (72.2% vs 34.9%), and more flame burns (19.5% vs 10.6%) compared to other Australian children. Streptococcus sp. infection risk was four times greater in Aboriginal and Torres Strait Islander children compared to other Australian children. Flame burns and high percentage total body surface area burns were a risk for Staphylococcus sp. and Streptococcus sp. infection in all children. The epidemiological profile for burn injuries managed in Australian burns centers differs between Aboriginal and Torres Strait Islander children and other children, indicating persistent health inequities. These differences should be considered in the development of injury prevention strategies and the clinical management of burn injuries for Aboriginal and Torres Strait Islander children and their families.